Análises das paisagens da ilha de Cotijuba: através do mapeamento das unidades geoambientais, Belém/PA - SILVA, Elias Klelington Leocádio Rodrigues da (Universidade Federal do Pará, 2023)
The present research looks at the Cotijuba Island, Belém / PA, located in the island region of the municipality of Belém. The study turns to the geoenvironmental theme from the integrated analysis of the landscape. The choice of this study area is justified, because in the last decades Cotijuba has undergone a rampant urbanization process, with irrational use of its resources, generating deforestation for the extraction of wood and removal of sand for civil construction. Thus, we sought to map the geoenvironmental units of Cotijuba Island, based on a survey of the elements that make up the landscape. The methodology followed the following steps: Bibliographic survey that enabled the survey of concepts that were guiding factors for the development of the research, Field study that allowed the survey of data and analyzes that are only possible with the measurement in loco, and Laboratory study that was essential to the development of the research, using techniques of remote sensing and geoprocessing that linked to the GIS allowed the making of all cartographic products presented in the research. For the mapping of land use and land cover classes, the Envi 5.1 software was used for supervised classification, extracting a Kappa index of 0.96. For the study of landscape metrics of forest fragments, the software arcgis 10.1 was used from the extension Partch Analyzes. In both procedures, the Sentinel-2 satellite image from the year 2018 was used. For the production of the MDEs, the Alos Palsar radar image was used, which allowed the analysis of the island's altimetry and slope. The mapping of the variables: geology, geomorphology and pedology, were carried out using information collected in the field and analysis of the results obtained from the products made in the Sentinel-2 and Alos Palsar image, based on Florenzano's remote sensing techniques methodology ( 2007). In view of this, the mapping of the Five Geoenvironmental Units of Cotijuba Island was made, highlighting their general characteristics. The results showed that Cotijuba needs a Management and Management plan on a municipal scale aimed at conserving natural resources and promoting the generation of jobs and income for the local community. In this sense, it is expected that the products raised here will serve as subsidies for them. Thus, ecotourism and the implementation of ecological corridors are suggested as measures to mitigate the problems presented here.